Cheilitis Granulomatosa - Rai Reena; Srinivas C R (Wolters Kluwer Medknow Publications, 2001)
Cheilitis granulomatosa is characterized by recurrent swelling of labial tissue which may be followed by permanent enlargement. We report a 35 year old man with cheilitis granulomatosa whose lesions regressed with clofazimine.